The Economics of Platform Liability - Yassine Lefouili; Leonardo Madio (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Public authorities in many jurisdictions are concerned about the proliferation of illegal content and products on online platforms. In this paper, we provide an economic appraisal of platform liability that highlights the effects of a stricter liability rule on several key variables such as prices, terms and conditions, business models, and investments. We also discuss the impact of the liability regime applying to online platforms on competition between them and the incentives of third parties relying on them. Finally, we analyze the potential costs and benefits of measures that have received much attention in recent policy discussions.
Keywords: K40; K42; K13; L22; L86; 330; liabilities rules; online platforms; illegal content and products; intellectual property